2010
DOI: 10.1172/jci41356
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule BDNF mimetics activate TrkB signaling and prevent neuronal degeneration in rodents

Abstract: Brain-derived neurotrophic factor (BDNF) activates the receptor tropomyosin-related kinase B (TrkB) with high potency and specificity, promoting neuronal survival, differentiation, and synaptic function. Correlations between altered BDNF expression and/or function and mechanism(s) underlying numerous neurodegenerative conditions, including Alzheimer disease and traumatic brain injury, suggest that TrkB agonists might have therapeutic potential. Using in silico screening with a BDNF loop-domain pharmacophore, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
311
2
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 374 publications
(339 citation statements)
references
References 64 publications
17
311
2
3
Order By: Relevance
“…37 Importantly, previous studies have shown that administration of the TrkB ligand, LM22A-4, binds and actives downstream signaling pathways including AKT and ERK, 13 and can ameliorate motor impairments in the model of both traumatic brain injury and stroke. 13,14 Consistent with this, we also report that multiple signaling pathways are activated in response to CX1837 and BDNF treatments, and include an increase in p-AKT, p-ERK, and p-MEK. As CREB deletion only partially blocked the recovery afforded by combined treatment of CX1837 and local BDNF delivery, other signaling pathways, in addition to the proposed AKT/GSK-3/CREB pathways, are likely to be playing a role in recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Importantly, previous studies have shown that administration of the TrkB ligand, LM22A-4, binds and actives downstream signaling pathways including AKT and ERK, 13 and can ameliorate motor impairments in the model of both traumatic brain injury and stroke. 13,14 Consistent with this, we also report that multiple signaling pathways are activated in response to CX1837 and BDNF treatments, and include an increase in p-AKT, p-ERK, and p-MEK. As CREB deletion only partially blocked the recovery afforded by combined treatment of CX1837 and local BDNF delivery, other signaling pathways, in addition to the proposed AKT/GSK-3/CREB pathways, are likely to be playing a role in recovery.…”
Section: Discussionmentioning
confidence: 99%
“…6 We have also shown that CX1837-mediated functional recovery occurred in a BDNF/TrkB-dependent manner, a finding that has been confirmed by Massa et al who further identified the role of downstream protein kinase B (AKT) and extracellular signalregulated kinase (ERK) signaling pathways. 13,14 One significant, issue that has yet to be addressed is whether CX1837 retains its effectiveness in aged populations, as it is now widely recognized that BDNF activity is significantly impaired with age. 15,16 As aging alters the responsiveness of the cortex, and how tropic factors may act, it is likely that cotreatments will afford greater recovery after stroke in aged populations.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for targeting TrkB in HD is based not only on BDNF deficiencies but also on multiple linkages between the receptor's signaling and underlying HD degenerative mechanisms. Our laboratories identified small molecule TrkB ligands with structures similar to loop II of BDNF (Massa et al, 2010), a region that confers TrkB activation and specificity (Longo and Massa, 2013). One such ligand, [N,NЈ,NЉ-tris(2-hydroxyethyl)-1,3,5-benzenetricarboxamide)] (LM22A-4), binds to TrkB but not other Trks or p75 NTR , and had a negative receptor binding screen (Cerep).…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral treatment with ampakines significantly improved respiratory function in male Mecp2 knockout mice [86], which phenocopies the recurrent apneas suffered by individuals with RTT. BDNF loop domain mimetics are small molecules designed in silico to interact with the BDNF binding pocket in the TrkB receptor [87]. One of them, LM22A-4, restored respiratory regularity in female Mecp2 heterozygous mice [88,89], increased dendritic spine density in CA1 pyramidal neurons in organotypic slice cultures of male Mecp2 knockout mice (Miller, Longo, and LP-M, in preparation), and restored long-term potentiation at CA3->CA1 excitatory synapses in hippocampal slices from symptomatic female Mecp2 heterozygous mice (Li, Longo, and LP-M, in preparation).…”
Section: Neurotrophins and Growth Factors: Brain-derived Neurotrophicmentioning
confidence: 99%